Economic Crisis and Class Divide: Analyzing Poverty and Inflation in Pakistan - Benazeer Chandio (Journal of Religion and Society, 2024)
Pakistan is facing an ongoing economic recession marked by continuous inflation, macroeconomic imbalance, and reemergence of poverty, leading to increasing inequality in the country. The research aims to evaluate the relationship between inflation and poverty in Pakistan with special emphasis on how inflation impacts poor individuals and classes differently than higher social strata. Inflation has always been a serious threat to the economic stability of a country; however, its negative impact increases when it leads to growing levels of poverty among the population. Secondary data gathered from the national and international reports, alongside scientific literature, will be utilized in the research. Qualitative methods will be used to analyze structural and economic factors that contribute to poverty in the context of inflation. The results show that high levels of inflation lead to reduced income and buying power and, as a consequence, lack of access to essential goods, including food productsIn addition to that, it has been found by the research that the phenomenon of inflation does not only contribute to an increase in the poverty rate but also causes an increase in income disparity, thus making socio-economic differences more prevalent. It has been estimated that poverty levels in Pakistan have increased to around 25%-28% over the past few years due to various factors like inflation, economic shocks, and vulnerabilities within the country’s economy, erasing all the progress that had previously been achieved in reducing poverty. Keywords: Inflation, Poverty, Economic Crisis, Class Divide, Income Inequality, Pakistan, Socio-economic Disparities, Purchasing Power, Economic Instability